Superhydrophobic ZnO networks with high water adhesion - Florica, Camelia (Springer, 2014)
ZnO structures were deposited using a simple chemical bath deposition technique onto interdigitated electrodes fabricated by a conventional photolithography method on SiO(2)/Si substrates. The X-ray diffraction studies show that the ZnO samples have a hexagonal wurtzite crystalline structure. The scanning electron microscopy observations prove that the substrates are uniformly covered by ZnO networks formed by monodisperse rods. The ZnO rod average diameter and length were tuned by controlling reactants' concentration and reaction time. Optical spectroscopy measurements demonstrate that all the samples display bandgap values and emission bands typical for ZnO. The electrical measurements reveal percolating networks which are highly sensitive when the samples are exposed to ammonia vapors, a variation in their resistance with the exposure time being evidenced. Other important characteristics are that the ZnO rod networks exhibit superhydrophobicity, with water contact angles exceeding 150° and a high water droplet adhesion. Reproducible, easily scalable, and low-cost chemical bath deposition and photolithography techniques could provide a facile approach to fabricate such ZnO networks and devices based on them for a wide range of applications where multifunctionality, i.e., sensing and superhydrophobicity, properties are required. PACS: 81.07.-b; 81.05.Dz; 68.08.Bc